583 DEFORMATION MAP OF LEFT VENTRICULAR STRAIN: COMPARISON BETWEEN PATIENTS WITH HYPERTROPHIC CARDIOMYOPATHY AND CONTROLS WITHOUT SIGNIFICANT CORONARY ARTERY STENOSIS. (15th December 2022) - Del Franco, AnnaMaria; Wierzbowska-drabik, Karina; Zampieri, Mattia; Palinkas, Eszter Dalma; Chiti, Chiara; Duraj, Iwona; Olivotto, Iacopo
Abstract: Background: Hypertrophic cardiomyopathy (HCM), being characterized by enhanced contractility, positively responses to treatment with myosin inhibitors which could promote reverse remodelling. Additionally, speckle tracking analysis highlights left ventricular (LV) contractile alterations in HCM, although the pathophysiological meaning and the effect of the target-therapy are still unclear. Aim: To analyse global and regional longitudinal peak systolic strain in patients with HCM in comparison to age-matched control group without HCM and with known coronary artery anatomy. Methods: We examined 37 HCM patients (33 with asymmetric septal and 4 with apical hypertrophy) and 67 age-matched controls without HCM or significant coronary stenoses, with transthoracic echocardiography with analysis of segmental and global left ventricular strain (GLS) by AFI method in 16-segment LV model. Results: Patients with HCM showed higher values of interventricular septal thickness, left atrial diameter and LV ejection fraction, whereas controls presented higher BMI and resting heart rate. In deformation analysis, GLS values were lower in HCM (15.9 ± 4.2 vs 18.4 ± 3.5%, p = 0.002) as well as segmental strain was significantly impaired in marker regions for studied form of HCM, in particular septal, inferior and inferolateral basal and mid segments as well as apical inferior segment for HCM with asymmetric septal hypertrophy; 4 patients with apical form of HCM showed severely impaired strain in all apical segments. Conclusions: Deformation analysis shows a significant impairment of global and segmental strain values in patients with HCM, in particular for hypertrophic segments. This finding does not definitely imply a certain contractile dysfunction, and further investigation on the effect of myosin inhibitors on strain analysis is strongly recommended.